2019
DOI: 10.13075/mp.5893.00879
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Polish version of the <i>Dizziness Handicap Inventory</i>

Abstract: Background:The Dizziness Handicap Inventory (DHI) was established to assess the impact of dizziness and balance problems on the quality of life. The aim of the study was to validate the Polish version of DHI for patients with vestibular disorders. Material and Methods: Two hundred and thirty patients diagnosed with vestibular impairment and/or positional vertigo were included in the study. The mean age of the study group was 56.2 years (SD = 13.6). The factor structure (the principal component analysis − PCA),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…No studies were found in which the primary goal was to assess the content validity of the English or translated versions of the DHI. However, the majority of studies which translated the DHI (20 out of 22) included some form of pilot testing for (one or more aspects of) the content validity, that is, relevance, comprehensiveness and/or comprehensibility (22,(25)(26)(27)29,32,34,35,37,38,42,43,(46)(47)(48)(49)51,54,57,58). We rated the methodological quality for these individual studies as ''doubtful,'' mainly because clear descriptions of the process of executing the cognitive interviews were lacking.…”
Section: Content Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…No studies were found in which the primary goal was to assess the content validity of the English or translated versions of the DHI. However, the majority of studies which translated the DHI (20 out of 22) included some form of pilot testing for (one or more aspects of) the content validity, that is, relevance, comprehensiveness and/or comprehensibility (22,(25)(26)(27)29,32,34,35,37,38,42,43,(46)(47)(48)(49)51,54,57,58). We rated the methodological quality for these individual studies as ''doubtful,'' mainly because clear descriptions of the process of executing the cognitive interviews were lacking.…”
Section: Content Validitymentioning
confidence: 99%
“…Comprehensibility of the DHI was addressed in 20 translation studies (22,(25)(26)(27)29,32,34,35,37,38,42,43,(46)(47)(48)(49)51,54,57,58). Overall, the patients in these studies had no difficulty understanding or answering the questions.…”
Section: Comprehensibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The DHI was originally developed in the English language for USA patients, but in the past decades, it has been translated and validated in many other languages, e.g., to German [ 9 ] or Spanish [ 10 ]. However, it has been observed that this questionnaire yields limited conclusions related to the clinically important information [ 8 , 10 , 11 ]. In the literature, a few studies have already concentrated on the relationship between the DHI score and (1) selected diseases or clinical status [ 12 , 13 ], and (2) vestibular testing objective methods [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are three subscales: Physical (P), Functional (F), and Emotional (E). Although it was originally written in English, DHI has been translated into many languages, e.g., Polish, German, Norwegian, Brazilian, and Spanish [ 20 ]. The other common, widely used questionnaire is the Vertigo Symptom Scale, published by Yardley in 1992.…”
Section: Methodsmentioning
confidence: 99%